Selected Plan Statistics February, 1963 - Planning Commission (Planning Commission, 1963)
This brochure presents selected statistics relating to Five Year Plans upto 1961-62, viz., physical targets and their achievements, Financial provision and actual outlay, contribution to national income and generation of additional employment. Figures for the period 1956-57 to 1961-62 are shown on an annual basis. The first three sections present the overall statistics and the subsequent sections the detailed breakdowns.. Some of the figures are still tentative and subject to revision.
Statistics and Surveys Division, Planning Commission, Government of India